Grid pricing of fed cattle - Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pricing fed cattle on a value-based quality and yield grade grid provides the best opportunity for cattle producers to receive premiums associated with high quality cattle. However, grid discounts for cattle not desired by the particular packer are often quite substantial. Thus, cattle producers targeting cattle for specific grids need to have considerable knowledge regarding the quality attributes of their cattle. This study compared pricing of 202 pens of fed cattle on a live basis, a carcass (dressed) basis, and using four different packer grids. Results indicate that no single pricing method is optimal for all cattle. Producers need to know the quality of cattle they have, be willing and able to sort those cattle, and compare the various selling options and grids before deciding upon the pricing method that generates the highest revenue.
Keywords: Beef; Grid pricing; Value-based pricing; Fed cattle prices